2017
DOI: 10.1055/s-0037-1600905
|View full text |Cite
|
Sign up to set email alerts
|

General Care of the Pregnant Patient in the Intensive Care Unit

Abstract: Pregnant women represent a small subset of all intensive care unit (ICU) admissions and may require intensive care for "obstetric" or "nonobstetric" reasons. Women may be admitted to the ICU at any stage of pregnancy or in the postpartum period. Pregnancy may be discovered at the time of admission to the ICU. Pregnancy impacts on ICU care in a variety of ways and requires a multidisciplinary approach to management. Pregnancy is associated with considerable physiological changes that affect most organ systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
0
11
0
1
Order By: Relevance
“…Guidelines for management are primarily derived from clinical experience -not clinical trials -and tend to focus on treatment of the maternal condition, with only general recommendations regarding fetal assessment and indications for delivery. 20 With respect to COVID-19 pneumonia, principles of care are most similar to patients with acute respiratory distress syndrome (ARDS), with modifications in medication regimens, target laboratory and physiologic parameters, and maternal positioning. 21 Decisions regarding frequency of fetal monitoring and/or delivery are governed by maternal status and gestational age, with the fetal cardiotocograph proposed to represent an additional "vital sign" to both guide and determine efficacy of therapy.…”
Section: The Case For Indicated Preterm Deliverymentioning
confidence: 99%
“…Guidelines for management are primarily derived from clinical experience -not clinical trials -and tend to focus on treatment of the maternal condition, with only general recommendations regarding fetal assessment and indications for delivery. 20 With respect to COVID-19 pneumonia, principles of care are most similar to patients with acute respiratory distress syndrome (ARDS), with modifications in medication regimens, target laboratory and physiologic parameters, and maternal positioning. 21 Decisions regarding frequency of fetal monitoring and/or delivery are governed by maternal status and gestational age, with the fetal cardiotocograph proposed to represent an additional "vital sign" to both guide and determine efficacy of therapy.…”
Section: The Case For Indicated Preterm Deliverymentioning
confidence: 99%
“…65 to PaCO 2 levels as high as 60 mm Hg. [71][72][73] As more cases of severe and critical COVID-19 pneumonia are managed in pregnant patients, multidisciplinary care among critical care, infectious disease, and maternal-fetal medicine specialists will be needed to ensure optimal outcomes for both mother and fetus.…”
Section: Cardiomyopathymentioning
confidence: 99%
“…In order to maintain appropriate uterine blood flow, PaCO 2 should be maintained >30 mm Hg 71 . Additionally maternal hypercapnia, PaCO 2 > 40 mm Hg, can lead to fetal respiratory acidosis; however, studies have not identified adverse outcomes in fetuses exposed to PaCO 2 levels as high as 60 mm Hg 71‐73 . As more cases of severe and critical COVID‐19 pneumonia are managed in pregnant patients, multidisciplinary care among critical care, infectious disease, and maternal‐fetal medicine specialists will be needed to ensure optimal outcomes for both mother and fetus.…”
Section: Clinical Course In Severe and Critical Illnessmentioning
confidence: 99%
“…In late stages of pregnancy, uteroplacental blood flow comprises a large part of the maternal cardiac output, making the fetus particularly sensitive to variations of maternal blood pressure. 34 For example, 3 patients underwent emergency cesarean sections due to signs of fetal distress, resulting in good outcome in 2 of them.…”
Section: Discussionmentioning
confidence: 99%